2008
DOI: 10.1111/j.1600-0609.2008.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of apoptosis‐related proteins and Ki‐67 in nasal NK / T‐cell lymphoma

Abstract: Objectives:  Nasal natural killer (NK)/T‐cell lymphoma is characterized by chemo‐resistance, angiodestruction, and aggressive tumor progression. Few studies exist on molecular characteristics of this disease entity. Methods:  Expression levels of major apoptosis‐related proteins Bcl‐2, Bcl‐x, Mcl‐1, Bax, and a proliferative marker Ki‐67 were analyzed in 11 nasal NK/T‐cell lymphoma cases by immunohistochemical methods. Nine cases were of NK‐cell lineage and two cases were of T‐cell lineage. For comparison, 12 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…Although patients whose tumors had ≥60% cells positive for Ki‐67 had a lower 3‐cycle rate of CR and lower 1‐year OS and PFS than did those whose tumors had <60% positive cells, the results were not statistically significant, and univariate analysis determined that a high Ki‐67 expression was not associated with a poor survival. This finding differs from those of previous studies 57, 58, 59, 60, 61, 62. Similarly, IPI score, disease stage, and expression of β2‐microglobulin and CD56, which have all been shown to be associated with survival for patients with nasal or extranasal NKTCL,59, 63, 64, 65, 66 were not associated with survival in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although patients whose tumors had ≥60% cells positive for Ki‐67 had a lower 3‐cycle rate of CR and lower 1‐year OS and PFS than did those whose tumors had <60% positive cells, the results were not statistically significant, and univariate analysis determined that a high Ki‐67 expression was not associated with a poor survival. This finding differs from those of previous studies 57, 58, 59, 60, 61, 62. Similarly, IPI score, disease stage, and expression of β2‐microglobulin and CD56, which have all been shown to be associated with survival for patients with nasal or extranasal NKTCL,59, 63, 64, 65, 66 were not associated with survival in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…A novel prognostic index incorporating B symptoms, clinical stage, serum LDH level and regional lymph node involvement has been described (Lee et al, 2006). Ki-67 expression has been also reported as a prognostic factor in patients with ENKL (Kim et al, 2007;Yasuda et al, 2009;Huang et al, 2014;He et al, 2014). However, in this study, univariate analysis indicated that stage was the only prognostic indicator for PFS and OS.…”
Section: Discussionmentioning
confidence: 60%
“…[22][23][24][38][39][40][41] Several small cohort of studies have demonstrated that a high EBV-DNA load is associated with advanced stage, poor clinical response, B-symptoms, and elevated LDH levels in NKTCL (supplemental Table 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). [31][32][33][34][35] Our results confirmed that pretreatment EBV-DNA levels correlate with B-symptoms, elevated LDH levels, and an IPI score of 1-2 in early-stage NKTCL.…”
Section: Discussionmentioning
confidence: 99%